World Economic Outlook, October 1989. (World Economic Outlook; World Economic Outlook ;, 1989)
This paper highlights that after two years of rapid growth in 1987 and 1988, there are now signs that the economic expansion in industrial countries is moderating to more sustainable rates. Inflation pressures have built up over 1988, reflecting high levels of resource utilization as well as certain temporary factors, but monetary conditions have been tightened substantially. Although the risk of a dangerous acceleration of inflation still exists, it appears to have diminished somewhat. Growth has also been strong in many developing countries, particularly exporters of manufactures.